Challenges and Strategies in Translating English Collocations into Kurdish: A Linguistic Approach - Zana Hama Amin (WISE Pendidikan Indonesia, 2023)
This study examines the challenges faced by Kurdish EFL learners in translating English collocations and explores strategies to enhance their translation competence. Using a mixed-methods approach, the research involved 20 fourth-year students from the University of Sulaimani, who were tested on their ability to translate 16 English collocations across six structural types: noun + noun, adjective + noun, verb + noun, verb + adverb, adverb + adjective, and noun + verb. The findings reveal a significant difficulty in translation, with only 35.31% of responses being correct. Students performed best in verb + adverb (90% accuracy) and noun + verb (75% accuracy) combinations, while adjective + noun (30%) and verb + noun (12.5%) collocations posed the greatest challenges. Qualitative analysis identified three primary issues: reliance on literal translation, cultural mismatches, and structural misalignment between English and Kurdish. For example, collocations like